2000
DOI: 10.1038/labinvest.3780153
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Structurally Unaltered Androgen Receptor in Extramammary Paget's Disease

Abstract: SUMMARY: Extramammary Paget's disease (EMPD) is an uncommon neoplasm of the skin that shows differentiation to an apocrine sweat gland. Although we previously showed that erbB-2 overexpression may play a part in the progression of EMPD, molecular genetic defects underlying the development of EMPD are poorly understood. In the study described here, we examined androgen receptor expression and gene alterations in 30 cases of EMPD without internal malignancy. Immunohistochemistry revealed that 24 of 30 (80%) case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 38 publications
1
16
1
Order By: Relevance
“…AR immunoreactivity was detected in 71% of the cases of extramammary Paget's disease. Previous studies also demonstrated that AR was detected in 54% [14] and 80% [15] of extramammary Paget's disease. ERa was detected in 29% of extramammary Paget's disease in our series.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…AR immunoreactivity was detected in 71% of the cases of extramammary Paget's disease. Previous studies also demonstrated that AR was detected in 54% [14] and 80% [15] of extramammary Paget's disease. ERa was detected in 29% of extramammary Paget's disease in our series.…”
Section: Discussionmentioning
confidence: 91%
“…Both ER and PR have been reported to be detected in some of the sweat gland neoplasms [13][14][15][16][17][18][19], but their isoforms have not been examined. ERb, which is widely distributed throughout the body [28], was detected in some sweat gland neoplasms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[330][331][332][333] Extramammary Paget's disease does not express estrogen or progesterone receptor antigenicity, but has been shown to express androgen receptor proteins as discussed above. 334,335 Differential expression of claudins, proteins involved in tight junction assembly in epithelial and endothelial cells, may differentiate cells of Paget's disease from adjacent squamous epithelia, but not from breast carcinoma cells. 336 Another form of Pagetoid intraepidermal carcinoma with vacuolated cells is sebaceous carcinoma, but in this entity the cells appear vacuolated, with a clear cytoplasmic morphology as opposed to basophilic mucin.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…It was reported that normal apocrine glands of the skin and mammary apocrine lesions contained no detectable estrogen receptors or progesterone receptors, but did express androgen receptors [1,2,3]. Recent studies demonstrated expression of androgen receptors in extramammary Paget’s disease [4, 5]. In contrast, lack of estrogen and progesterone receptors has been reported in extramammary Paget’s disease [5,6,7,8].…”
Section: Introductionmentioning
confidence: 98%